The state of the agri-, food-, and climate-tech innovation ecosystem in Uzbekistan - Vitón, Roberto; Garzaron, Lucia; Menza, Gianpiero; Zaccari, Claudia; Dolinga, Moritz (2025)
Since 2016, Uzbekistan has embarked on a transformative journey of economic reform. With the liberalization of currency, attraction of foreign direct investment, and the removal of state-imposed quotas and subsidies, Uzbekistan has laid the groundwork for a more dynamic, market-based economy. Amid this ongoing transformation, innovation has emerged as a key driver of sustainable agricultural development in the country. In 2017, the government established the Ministry of Innovative Development (now part of the Ministry of Higher Education, Science, and Innovation) and other targeted programs, demonstrating a clear political will to support the creation and scaling of homegrown solutions, including those in the agri-, food- and climate-tech space.